THE INFLUENCE OF TEXT TWIST GAME TOWARDS STUDENTSâ VOCABULARY MASTERY AT THE FIRST SEMESTER OF THE TENTH CLASS AT SMA ADIGUNA BANDAR LAMPUNG IN 2012/2013 - Damiri, Adenan (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2013)
The objective of learning English in Senior High School is to enable students to use English as a means of communication, in spoken and written form. To support those skills they should master four skills of language, namely: listening, speaking, writing and reading and components of language such as vocabulary, structure, spelling and pronunciation. Studentsâ vocabulary mastery is influenced by many factors. One of them is the technique, which the teacher uses in teaching. In this research, the writer applied Text Twist Game in teaching vocabulary in the classroom. Then writer analyzed the result of the technique in order to know its influence. The objective of this research is to know whether there is positive influence of Text Twist Game in teaching vocabulary.From the distribution list with df= 68 obtained the t-ratio= 4.89 or significant level of 5% is equal to 2.00. And t ratio t0.95 or significant level of 1% is equal to 2.66. And according to the good examination criterion for the significance level of 5% and 1%. So the writer could conclude that there is positive influence of Text Twist Game towards studentsâ vocabulary mastery at the first semester of the tenth class at SMA Adiguna Bandar Lampung in 2012/2013 and the average score of the studentsâ vocabulary mastery who were taught by using Text Twist Game was higher than the average score of the studentsâ vocabulary mastery who were taught without Text Twist Game at the first semester of the tenth class at SMA Adiguna Bandar Lampung in 2012/2013.